2007
DOI: 10.1248/cpb.55.308
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XII.1) New Spirostane-Type Steroid Saponins with Antidiabetogenic Activity from Borassus flabellifer

Abstract: The Palmae plant, Borassus flabellifer L. (palmyra palm in English), is widely distributed and cultivated in tropical Asian countries such as Thailand, Bangladesh, India, Myanmar, Sri Lanka, Malaysia, etc. The fruit pulp of B. flabellifer has been used in traditional dishes and the sap, which was trapped from the flower part, has been used as a sweetener for diabetic patients. In the previous studies, several steroidal saponins, 2-4) a polysaccharide, 5) and a triterpene 6) constituents were isolated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
92
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 40 publications
6
92
0
3
Order By: Relevance
“…10,11) Furthermore, those oligoglycosides were found to exhibit antiallergic, 6) antidiabetic, 7) antiobesitic, 5,8) gastroprotective, 7,10,11) and platelet aggregation 10,11) activities. In the course of our characterization studies on Camellia speicies [12][13][14][15] and medicinal flowers, [16][17][18][19][20][21] we found that the methanolic (MeOH) extract and its 1-butanol (1-BuOH)-soluble fraction from the flower buds of C. oleifera showed gastroprotective effects on ethanol-or indomethacin-induced gastric mucosal lesions in rats. The 1-BuOH-and ethyl acetate (EtOAc)-soluble fractions exhibited inhibitory activities on rat lens aldose reductase and scavenging effects on 1,1-diphenylpicryl-2-hydrazyl (DPPH) radical and superoxide.…”
mentioning
confidence: 99%
“…10,11) Furthermore, those oligoglycosides were found to exhibit antiallergic, 6) antidiabetic, 7) antiobesitic, 5,8) gastroprotective, 7,10,11) and platelet aggregation 10,11) activities. In the course of our characterization studies on Camellia speicies [12][13][14][15] and medicinal flowers, [16][17][18][19][20][21] we found that the methanolic (MeOH) extract and its 1-butanol (1-BuOH)-soluble fraction from the flower buds of C. oleifera showed gastroprotective effects on ethanol-or indomethacin-induced gastric mucosal lesions in rats. The 1-BuOH-and ethyl acetate (EtOAc)-soluble fractions exhibited inhibitory activities on rat lens aldose reductase and scavenging effects on 1,1-diphenylpicryl-2-hydrazyl (DPPH) radical and superoxide.…”
mentioning
confidence: 99%
“…3,11,12,17,18) The 1 H-and 13 C-NMR (CD 3 OD, Table 1) spectra of 1, which were assigned by various NMR experiments, 21) showed signals assignable to two The connectivities of glycopyranosyl parts were determined by a heteronuclear multiple-bond correlations (HMBC) experiment on 1. Namely, long-range correlations were observed between the terminal-Glc-1-proton (1Љ-H) and the inner-Glc-6-carbon (d C 69.5, 6Ј-C) and between the innerGlc-1-proton (1Ј-H) and the angeloyl ester carbonyl carbon (d C 167.7, 1-C) (Fig.…”
Section: Structures Of Everlastosides F (1) G (2) and H (3)mentioning
confidence: 99%
“…The H 2 Oeluted fraction was subjected to HPLC analysis under the following conditions: HPLC column, Kaseisorb LC NH 2 -60-5, 250ϫ4.6 mm i.d. (Tokyo Kasei Co., Ltd., Tokyo, Japan); detection, optical rotation [Shodex OR-2 (Showa Denko Co., Ltd., Tokyo, Japan); mobile phase, CH 3 …”
Section: Alkaline and Acid Hydrolysis Of Everlastosides F (1) G (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dioscorea plants are important agricultural crops in tropical regions, grown for their large tubers in parts of Africa, Asia, and Oceania (Oke 1972). The rhizome of Dioscorea nipponica Makino has high saponin content and use in folk medicine as treatment for coronary heart disease, asthma, rheumatoid arthritis, and hyperlipidemia, as well as a source of hormonal sterol synthesis precursors (Yoshikawa et al 2007). Recently, studies revealed that Dioscorea plant extracts exert antiobesity effects (Kwon et al 2003;Xiao et al 2010).…”
Section: Introductionmentioning
confidence: 99%